Bone Mesenchymal Stem Cells Promote Extracellular Matrix Remodeling of Degenerated Nucleus Pulposus Cells via the miR-101-3p/EIF4G2 Axis - Wang, Zeng; Ding, Xiaolin; Cao, Feifei; Zhang, Xishan; Wu, Jingguo (Frontiers in Bioengineering and Biotechnology, 2021)
The etiology of lumbocrural pain is tightly concerned with intervertebral disc degeneration (IDD). Bone mesenchymal stem cells (BMSCs)-based therapy bears potentials for IDD treatment. The properties of microRNA (miRNA)-modified BMSCs may be altered. This study investigated the role and mechanism of BMSCs promoting extracellular matrix (ECM) remodeling of degenerated nucleus pulposus cells (NPCs) via the miR-101-3p/EIF4G2 axis. NPCs were collected from patients with IDD and lumbar vertebral fractures (LVF). The expressions of miR-101-3p and ECM-related proteins Col-I and Col-II were detected using RT-qPCR. The expressions of Col-I and Col-II, major non-collagenous component Aggrecan, and major catabolic factor MMP-13 were detected using Western blotting. BMSCs were co-cultured with degenerated NPCs from IDD patients. Viability and apoptosis of NPCs were measured using MTT assay and flow cytometry. After the degenerated NPCs were transfected with miR-101-3p inhibitor, the expressions of ECM-related proteins, cell viability, and apoptosis were detected. The targeting relationship between miR-101-3p and EIF4G2 was verified. Functional rescue experiments verified the effects of miR-101-3p and EIF4G2 on ECM remodeling of NPCs. Compared with the NPCs of LVF patients, the degenerated NPCs of IDD patients showed downregulated miR-101-3p, Col-II, and Aggrecan expressions, and upregulated MMP-13 and Col-I expressions. BMSCs increased the expressions of miR-101-3p, Aggrecan, and Col-II, and decreased the expressions of MMP-13 and Col-I in degenerated NPCs. BMSCs enhanced NPC viability and repressed apoptosis. Downregulation of miR-101-3p suppressed the promoting effect of BMSCs on ECM remodeling. miR-101-3p targeted EIF4G2. Downregulation of EIF4G2 reversed the inhibiting effect of miR-101-3p inhibitor on ECM remodeling. In conclusion, BMSCs increased miR-101-3p expression in degenerated NPCs to target EIF4G2, thus promoting the ECM remodeling of NPCs.